LOCAL WISDOM IN THE STORY OF NENE LUHU: LITERATURE RECEPTIONS OF THE MALUKU COMMUNITY - Andi Masniati (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2023)
AbstractThis research aims to examine local wisdom in the folk tale of Nene Luhu, which is one of the folk stories from Maluku. This study employs an experimental synchronous reception research with a structural approach to assess respondents' reception of the structure and local values in the Nene Luhu story. The sample consists of productive-aged individuals in Maluku, specifically those aged 18-25, comprising both males and females who have read or heard the Nene Luhu story. The results of the research indicate that the Nene Luhu story vividly portrays values of diversity, tradition, archipelagic wisdom, and the rich and diverse customs of Maluku. The narrative also conveys moral messages emphasizing the importance of trust, justice, loyalty, courage, and environmental care. In conclusion, the Nene Luhu story is not merely a narrative but also a reflection of noble values and wisdom inherent in Maluku cultureKeywords: Nene Luhu, values, local, wisdom, diversity